Faktor-Faktor yang Berhubungan dengan Kejadian Preeklamsia pada Ibu Hamil di Rumah Sakit Muhammadiyah Palembang Tahun 2021 - Putri Ramadona; Pradiva Dwi Lestari; Hazairin Effendi (Universitas Batanghari Jambi, 2022)
In Indonesia, the MMR is still relatively high. In general, the main causes of death are complications of pregnancy/delivery, namely bleeding 42%, eclampsia/preeclampsia 13%, abortion 11%, infection 10%, prolonged labor/labor stuck 9% and other causes 15%. Preeclampsia is still a problem that threatens pregnancy, especially in developing countries. Risk factors that can increase cases of preeclampsia include parity, extreme age and disease history. The purpose of this study was to determine the factors that influence the incidence of preeclampsia in pregnant women at Muhammadiyah Hospital Palembang in 2021. Design Quantitative research using an analytical survey method with a cross sectional approach. The population in this study were all pregnant women who had their pregnancy checked at Muhammadiyah Hospital Palembang in 2021 from January-May a total of 718 mothers with a sample of 88 mothers who were randomly selected by random sampling. Data analysis used univariate and bivariate analysis. The results showed that there was a relationship between maternal age (Pvalue = 0.035), parity (Pvalue = 0.035) and gestational age (Pvalue = 0.004) with the incidence of preeclampsia in pregnant women at Muhammadiyah Hospital Plembang in 2021. In conclusion, there was a significant relationship between maternal age, parity, and gestational age with the incidence of preeclampsia at the Palembang Muhammadiyah Hospital in 2021. It is hoped that the results of this study can be an illustration for health care providers to improve health quality, especially dealing with the incidence of preeclampsia.